2023
DOI: 10.1111/pbi.13971
|View full text |Cite
|
Sign up to set email alerts
|

Plant nitrogen availability and crosstalk with phytohormones signallings and their biotechnology breeding application in crops

Abstract: Summary Nitrogen (N), one of the most important nutrients, limits plant growth and crop yields in sustainable agriculture system, in which phytohormones are known to play essential roles in N availability. Hence, it is not surprising that massive studies about the crosstalk between N and phytohormones have been constantly emerging. In this review, with the intellectual landscape of N and phytohormones crosstalk provided by the bibliometric analysis, we trace the research story of best‐known crosstalk between N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 177 publications
0
8
0
Order By: Relevance
“… and are absorbed and converted by the nitrate peptide transporter family/transporters (NPF/NRTs) protein family and ammonium transporters (AMTs) protein family in plants, respectively. Most of is transported to ammonium nitrogen by NR and NiR in plants, which is further assimilated to organic form by GS/GOAT for the biosynthesis of nitrogenous compounds in plants ( Xing et al., 2022 ). Nhd1 can directly bind to the promoters of OsAMT1.3 and OsNRT2.4 , activating their expression and regulating the uptake and partitioning of and in rice, thus affecting the uptake and utilization of N in rice ( Li et al., 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“… and are absorbed and converted by the nitrate peptide transporter family/transporters (NPF/NRTs) protein family and ammonium transporters (AMTs) protein family in plants, respectively. Most of is transported to ammonium nitrogen by NR and NiR in plants, which is further assimilated to organic form by GS/GOAT for the biosynthesis of nitrogenous compounds in plants ( Xing et al., 2022 ). Nhd1 can directly bind to the promoters of OsAMT1.3 and OsNRT2.4 , activating their expression and regulating the uptake and partitioning of and in rice, thus affecting the uptake and utilization of N in rice ( Li et al., 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 18 DEGs obtained from leaf transcriptome, 12 and 3 genes were down‐ and up‐regulated by low N (0.04 or 0.1 m m NO 3 − ) in all four sets of leaf transcriptome data, respectively (Figure 3d; Table S8). It is well known that phytohormones play essential roles in response to N availability (Xing et al., 2023). We found that ZmCKX1 0 ( Zm00001eb040280 ) encoding cytokinin dehydrogenase and an auxin‐responsive gene, ZmIAA20 ( Zm00001eb213730 ) were located in 195–213.2 Mb and 4.4–39.3 Mb hotspots on chromosomes 1 and 5, respectively (Figure 3e; Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…Plant roots have evolved different systems for nitrogen uptake. Auxin, CTK, ABA, ETH, GA, BR, and JA can regulate NO3− and NH4+ uptake by regulating the transcript levels or transport activities of the NPF/NRT1, NRT2, and AMTs families in various plants [ 91 ]. In addition, JA can also mediate the expression of OsWRKY28 to enhance rice root elongation and phosphate absorption [ 92 ].…”
Section: Myc2 Is Involved In the Regulation Of Plant Growth And Devel...mentioning
confidence: 99%